The role of the environment in human rights: the challenges faced by the Muslim Ummah - Zul'azmi Yaakob; Zailan Moris (Universiti Kebangsaan Malaysia, 2014)
The term ‘environment’ refers to both the natural world as well as the surroundings of and influences on a particular thing. The environment plays a major role and influence on human beings and their lives. This article discusses the influential role the environment plays in relation to human rights. Today, human rights is a global issue and the rights that are advocated range from the basic human needs of food and shelter to the right of freedom of speech to the more religiously contentious gay rights. This paper contends that the issue of human rights is closely connected to the environment or the social conditions of a particular community; specifically the values and principles which dominate and determine the worldview of that community or society. In the context of our global society, the issue of deciding the content and nature of human rights is extremely challenging, especially to religious societies and communities, since religious principles and values are no longer a dominant factor in determining what is right or wrong, good or bad. This is the situation faced by the Muslim ummah. Many of the rights advocated by the modern West which it considers to be fundamental, universal and human are contrary to Islamic principles and values. For example, the right of freedom of speech to insult and mock the sacred tenets in religious teachings, the right to gay marriages which run contrary to natural laws, and the right to exploit natural resources for economic development without regard to the rights of other creatures which also inhabit this world. Thus, the Muslim ummah is in a dilemma as to whether to adapt itself to the modern and secular global environment or change its environment to advocate its Islamic worldview and understanding of human nature, rights, responsibilities and freedom.